The influence of acceleration on the efficiency of sand compaction tests conducted on a vibrating table = Wpływ przyspieszenia na efektywność zagęszczania piasku na stole wibracyjnym - Szajna, Waldemar St. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents a standard vibrating table for fresh concrete testing adopted for determination of maximum dry density (&Rho[indeks dolny - ?dmax?]) of sand. Vibration is an efficient method for coarse soil compaction therefore vibrating tables are useful for (&Rho[indeks dolny - ?dmax?]) determination.
Keywords: concrete mix; sand compaction; vibrating table; mechanical vibration measurements; density - acceleration relationship; mieszanka betonowa; zagęszczenie piasku; stół wibracyjny; pomiar drgań mechanicznych; efektywność zagęszczania